The effect of preload, density and thickness on seat dynamic stiffness - Mohammad Hassan, Azmi; Md Rezali, Khairil Anas; Abdul Jalil, Nawal Aswan; As’arry, Azizan; Azizan, Mohd Amzar (Universiti Putra Malaysia, 2022)
The vibration transferred to the car floor transmits to the human body through the seat structure, and the typical design of the seat structure consists of several components such as seat frame and seat cushion. The material widely used as seat cushion is open-cell polyurethane (PUR) foam; when under vibration, it will behave dynamically. Factors such as mechanical properties and material thickness of PUR can affect its behaviour and performance and the amount of vibration transmits to the human body. This work measures the PUR dynamic stiffness for different material densities and thicknesses. The test was conducted using an indenter head with a flat surface since it was a less expensive method, and quicker measurement could be done. The force sensor was placed within the indenter structure to measure the load transmitted to the seat and acceleration data acquired by the accelerometer, which was mounted on a shaker test plate. Foam materials with 30 kg/m3 and 44 kg/m3 with 30 mm and 50mm thickness are used in the experiment with the amount of preload applied of 20 N,30 N and 40 N. Seat stiffness increased when the preload increased from 20 N to 40 N, and a similar trend occurred when foam thickness decreased. The lower density of PUR resulted in a greater increase of seat stiffness and damping across the frequency 0-30 Hz compared to a higher density of PUR. This study concluded that thickness, preload, and density significantly affect seat dynamic stiffness.